PERAN PENGAWAS SEBAGAI SUPERVISOR DAN ADMINISTRATOR (STUDI KASUS DI MAN 2 TULUNGAGUNG) - Rohmat, Rohmat (PEDAGOGY, 2017)
Administration and supervision can not be separated, but in certain cases they are distinguishable. In socialize and organize, in cooperation has a central position as the essence of social life and organization is the cooperation agreement including a supervisor / sepervisor with the principal and the teachers. Even in the empowerment of organizations, cooperation is the ultimate goal of any development program. A supervisor / supervisor at least can be measured against the success of how well he creates cooperation within the organization (internal), and collaborates with parties outside the organization (external).